The Effect of a Triple Combination of Bevacizumab, Sodium Hyaluronate and a Collagen Matrix Implant in a Trabeculectomy Animal Model - Vanessa Andrés-Guerrero; Irene Camacho-Bosca; Liseth Salazar-Quiñones; Nestor Ventura-Abreu; Mercedes Molero-Senosiain; Samuel Hernández-Ruiz; Guillermo Bernal-Sancho; Rocío Herrero-Vanrell; Julián García-Feijóo (MDPI AG, 2021)
Currently available anti-scarring treatments for glaucoma filtration surgery (GFS) have potentially blinding complications, so there is a need for alternative and safer agents. The effects of the intrableb administration of a new combination of the anti-VEGF bevacizumab, sodium hyaluronate and a collagen matrix implant were investigated in a rabbit model of GFS, with the purpose of modulating inflammation, angiogenesis, fibroblast migration and fibrogenesis in the wound healing process. A comparative-effectiveness study was performed with twenty-four rabbits, randomly assigned to the following treatments: (a) biodegradable collagen matrix implant (Olo), (b) bevacizumab-loaded collagen matrix implant (Olo-BVZ), (c) bevacizumab-loaded collagen matrix implant combined with sodium hyaluronate (Olo-BVZ-H5) and (d) sham-operated animals (control). Rabbits underwent a conventional trabeculectomy and were studied over 30 days in terms of intraocular pressure and bleb characterization (height, area and vascularity in central, peripheral and non-bleb zones). Histologic differences among groups were further evaluated at day 30 (inflammation, total cellularity and degree of fibrosis in the area of surgery). Local delivery of bevacizumab (Olo-BVZ and Olo-BVZ-H5) increased the survival of the filtering bleb by 21% and 31%, respectively, and generated a significant decrease in inflammation and cell infiltration histologically 30 days after surgery, without exhibiting any local toxic effects. Olo-BVZ-H5 showed less lymphocyte infiltration and inflammation than the rest of the treatments. Intraoperative intrableb implantation of bevacizumab, sodium hyaluronate and a collagen matrix may provide an improved trabeculectomy outcome in this model of intense wound healing. This study showed an effective procedure with few surgical complications and a novel combination of active compounds that offer new possibilities to improve the efficacy of filtration surgery.